Epithelial SIRT6 governs IL-17A pathogenicity and drives allergic airway inflammation and remodeling - Quan, Jingyun; Wen, Xiaoxia; Su, Guomei; Zhong, Yu; Huang, Tong; Xiong, Zhilin; Huang, Jiewen; Lv, Yingying; Li, Shihai; Luo, Shuhua; Luo, Chaole; Cai, Xin; et al. (Nature communications, 2023)
Dysregulation of IL-17A is closely associated with airway inflammation and remodeling in severe asthma. However, the molecular mechanisms by which IL-17A is regulated remain unclear. Here we identify epithelial sirtuin 6 (SIRT6) as an epigenetic regulator that governs IL-17A pathogenicity in severe asthma. Mice with airway epithelial cell-specific deletion of Sirt6 are protected against allergen-induced airway inflammation and remodeling via inhibiting IL-17A-mediated inflammatory chemokines and mesenchymal reprogramming. Mechanistically, SIRT6 directly interacts with RORγt and mediates RORγt deacetylation at lysine 192 via its PPXY motifs. SIRT6 promotes RORγt recruitment to the IL-17A gene promoter and enhances its transcription. In severe asthma patients, high expression of SIRT6 positively correlates with airway remodeling and disease severity. SIRT6 inhibitor (OSS_128167) treatment significantly attenuates airway inflammation and remodeling in mice. Collectively, these results uncover a function for SIRT6 in regulating IL-17A pathogenicity in severe asthma, implicating SIRT6 as a potential therapeutic target for severe asthma. IL-17 mediated inflammation in the lung is mediated by different effector molecules. Here the authors show that the epigenetic regulator epithelial sirtuin 6 (Sirt6) is associated with lung inflammation in asthma patients and that Sirt6 contributes to promotion of inflammation in mouse asthma models.